Urban Heat Island Mitigation Technologies - Emmanuel, Rohinton (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is relevant to architects, urban designers, planners, and policy makers concerned with enhancing climate-sensitive urban form and planning. It discusses building and neighborhood design: layout and design features that maximize energy efficiency and thermal comfort without compromising the ability of other buildings to enjoy similar benefits; the use of interstitial spaces (piazzas, streets, and parks) to improve the microclimate at the neighbourhood-level; design intervention case studies; innovative uses of interstitial spaces to improve the local climate at the neighborhood level; and urban radiative cooling solutions to mitigate the unintended climate consequences of urban growth and suggestions for ways forward.